Current Population Survey, May 1983: Pension and Retirement Plan Coverage ([Verlag nicht ermittelbar], 1985)
This data collection supplies standard monthly labor force data for the week prior to the survey. Comprehensive information is given on the employment status, occupation, and industry of persons 14 years old and older. Additional data are available concerning weeks worked and hours per week worked, reason not working full-time, total income and income components, and residence. This dataset also contains supplemental information on pension and retirement plan coverage through employer- or union-sponsored retirement plans as well as individual retirement plans and Keogh plans. Information on demographic characteristics, such as age, sex, race, household relationship, and Hispanic origin, is available for each person in the household enumerated.